Deposition records of persistent organic pollutants and black carbon in dated sediment cores from China marginal seas: Implications for terrestrial sources and transport processes. (August 2022) - Lin, Tian; Han, Yizhen; Wu, Zilan; Hu, Limin; Rose, Neil L.; Guo, Zhigang
Abstract: Black carbon (BC) and persistent organic pollutants (POPs) were analyzed from three sediment cores collected offshore in the East China Marginal Seas. The results showed steadily increasing or stable BC concentrations and fluxes. By contrast, time trends of POPs fluxes were consistent with historical records of commercial production and use in China. Although the POP inventories decreased significantly with increase in offshore distance, the relatively consistent trends for individual POPs in different sea areas confirmed that the main sources are derived from mainland China and that atmospheric input was an important contribution. POPs inventories decreased by 59–91 % during transport from the Yellow Sea to the remote East China Sea and deposition to the sediment. This suggests that the source signal for POPs may be preserved under stable depositional environments, even though only a fraction of those pollutants are buried in open sea sediments. Highlights: BC and POPs were analyzed from three sediment cores collected offshore in the ECMSs. Compared with BC, there was a significant loss of POPs during transport in the water column. Source signals may be better preserved although only a fraction is buried in the sediment.